2011
DOI: 10.1177/0363546511405024
|View full text |Cite
|
Sign up to set email alerts
|

Double-Bundle versus Single-Bundle Anterior Cruciate Ligament Reconstruction

Abstract: This 2-year randomized trial showed that the revision rate of the anterior cruciate ligament reconstruction was significantly lower with the double-bundle technique than that with the single-bundle technique. However, additional years of follow-up are needed to reveal the long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 44 publications
(29 reference statements)
3
25
0
Order By: Relevance
“…For instance, Tiamklang et al 34 found 6 studies presenting data on graft failure in their Cochrane meta-analysis, and there was no significant difference between double- and single-bundle ACL reconstruction. Moreover, Björnsson et al 5 found a trend toward fewer reruptures, and Suomalainen et al 32 , 33 found significantly fewer graft failures and subsequent revision ACL surgery after double-bundle ACL reconstruction than after single-bundle surgeries at 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tiamklang et al 34 found 6 studies presenting data on graft failure in their Cochrane meta-analysis, and there was no significant difference between double- and single-bundle ACL reconstruction. Moreover, Björnsson et al 5 found a trend toward fewer reruptures, and Suomalainen et al 32 , 33 found significantly fewer graft failures and subsequent revision ACL surgery after double-bundle ACL reconstruction than after single-bundle surgeries at 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[78] Variability in healing was observed in these studies but longer follow-ups indicated a complete structural and morphological resemblance to the native ACL. [7982] A significant delay in returning to sport following ACLR to nearly two years may allow complete healing of the ACL graft and possibly the prevention of early failure in ACLR knees.…”
Section: Biological Recovery Of the Kneementioning
confidence: 99%
“…Some studies have additionally found that their DB ACL reconstruction group had fewer notchplasties5 and better visual analog scale6 and knee scores than its SB counterpart 6,7,13,17,18. Suomalainen et al15,16 reported that their DB group had a lower reoperation rate due to graft failure and, in their 8-year study, Zaffagnini et al18 also reported a lower reoperation rate in their DB group, although in that study there were also knee problems other than graft ruptures. They concluded that the DB method resulted in less OA and a better range of motion than the SB ACL reconstruction method.…”
Section: Discussionmentioning
confidence: 99%
“…A graft was considered visible when intact graft fibers were seen, partially visible when only few graft fibers were seen (Figure 3), and invisible when no graft fibers were seen (Figure 4). 15…”
Section: Methodsmentioning
confidence: 99%